Gastric adenocarcinoma advanced in a final-year student. A case report. - Imri Vishi; Agron Dogjani; Ragip Bytyqi; Sami Spahiu; Nijazi Vishi (Albanian Journal of Trauma and Emergency Surgery, 2018)
Introduction: Gastric carcinoma, while most common in the 50-70 age group [2], is an infrequent occurrence under the age of 30. This rarity should not lead to complacency, as it can still occur, and when it does, it tends to grow rapidly and steadily to reach higher levels in older age groups [3]. There are two subtypes of adenocarcinoma arising from the gastric mucosa: intestinal and diffuse, based on Lauren (1965) criteria.